อิทธิพลของโซเดียมคลอไรด์ต่ออัตราการสังเคราะห์ด้วยแสง และปริมาณพอลิเอมีนในข้าว Oryza sativa L. - สุวัฒน์ ธีระพงษ์ธนากร (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The experiment was conducted to investigate some physiological characters, growth parameters and polyamine contents in leaves of rice plants during short-and long-term periods after sodium chloride treatments. Four rice cultivars Pokkali (salt-tolerant), PTT85180, RD6 (moderately tolerant) and IR28 (salt-sensitive) were use in this study. Physiological characters (A, Gs, E, CE and QY) of rice plants were found to be higher in Pokkali, PTT85180 than RD6 and IR28 during short and long-term periods after sodium chloride treatments. The growth parameters (RGR, leaf area, shoot and root dry weight) of all salinized cultivars were significantly decreased during 7-21 days of salinity levels. The critical concentration was found in 50 mMNaCI level. However, the carboxylation efficiency of rice growth was found to be the highest in Pokkali while PTT85180, RD6 and IR28 showed moderate and lowest levels respectively after salinity stress. Pokkali, PTT85180, and RD6 cultivars accumulated high levels of Spd and Spm resulting in enhanced level of total polyamine while IR28 cultivar accumulated lower levels of those than the other when exposed to salinity stress during 14-21 days. The ratio of Put/Spd+Spm was found to be higher เท IR28 cultivar than Pokkali, PTT85180 and RD6 after 14 days of salinization. The interrelations between physiological characters (A, Gs, E, CE and QY) and growth parameters (RGR, leaf area, shoot and root dry weight) were negatively correlated to salinity stress. Contrastly, salinity levels were positively correlated with polyamine, WUE and SLW respectively. in summary, changes in physiological characters, growth parameters and polyamine contents in leaves were correlated with salt tolerance of rice in each cultivars.